Student Mathematic Connection Ability Through Ict Assisted Preprospec Learning Model - Iswara, Ranggamurti; Rachmani Dewi, Nuriana; Cahyono, Adi Nur (Universitas Negeri Semarang, 2021)
There are five standard processes in learning mathematics, one of which is connection. In SMK mathematics learning, the ability to connect mathematics is needed by students, namely in mathematics itself, in subjects other than mathematics, as well as in solving real-life problems. Mathematical problem solving requires the ability to connect mathematics to able to connect between mathematical ideas to find solutions to problems. Self-confidence is one of several character values that are cultivated in learning. To face a problem requires an attitude of confidence in one's abilities. This attitude can affect students' motivation and performance in mathematics learning. Thus, the ability to connect mathematics and self-confidence have an important role in learning mathematics. The purpose of this study was to determine whether the PREPROSPEC learning model was effective in terms of the students' mathematical connection abilities. This research is a type of mixed-method research. The research design the researchers chose was quasi-experimental. The population in this study were students of class XI SMK Negeri 1 Purbalingga majoring in TKJ 2020/2021 academic year. The results showed that the ICT-assisted PREPROSPEC learning model was effective on the student's connection ability. This learning model has the advantage of being more flexible in its application. In addition, the additional use of ICT is expected to help students develop mathematical connection skills more easily.